The Routledge handbook of literature and space - Tally, Robert T., Jr (New York, 2017)
The "spatial turn" in literary studies is transforming the way we think of the field. The Routledge Handbook of Literature and Space maps the key areas of spatiality within literary studies, offering a comprehensive overview but also pointing towards new and exciting directions of study. The interdisciplinary and global approach provides a thorough introduction and includes thirty-two essays on topics such as: Spatial theory and practice - Critical methodologies - Work sites - Cities and the geography of urban experience - Maps, territories, readings. The contributors to this volume demonstrate how a variety of romantic, realist, modernist, and postmodernist narratives represent the changing social spaces of their world, and of our own world system today.